Susceptibility of penicillin-susceptible and -resistant pneumococci to dirithromycin compared with susceptibilities to erythromycin, azithromycin, clarithromycin, roxithromycin, and clindamycin. - Visalli, M A (1997)
Agar dilution with incubation in air and CO2 was used to determine the MICs of erythromycin, dirithromycin, azithromycin, clarithromycin, roxithromycin, and clindamycin for 79 penicillin-susceptible, 72 penicillin-intermediate, and 74 penicillin-resistant pneumococci (158 erythromycin-susceptible and 67 erythromycin-resistant pneumococci). MICs obtained in air were usually 1 to 3 dilutions lower than those obtained in CO2. In air, the respective MICs at which 50% (MIC50s) and 90% (MIC90s) of penicillin-susceptible, -intermediate, and -resistant strains are inhibited were as follows: erythromycin, 0.016 and 0.5, 0.03 and > 64, and 2 and > 64 microg/ml; dirithromycin, 0.03 and 0.5, 0.06 and > 64, and 8 and > 64 microg/ml; azithromycin, 0.03 and 0.5, 0.06 and > 64, and 2 and > 64 microg/ml; clarithromycin, 0.016 and 0.06, 0.03 and > 64, and 2 and > 64 microg/ml; roxithromycin, 0.06 and 2, 0.06 and > 64, and 2 and > 64 microg/ml; and clindamycin, 0.03 and 0.06, 0.06 and > 64, and 0.06 and > 64 microg/ml. The MICs of erythromycin, azithromycin, and dirithromycin were very similar; however, clarithromycin MICs were generally 1 to 2 dilutions lower and roxithromycin MICs were 1 to 2 dilutions higher than those of the other compounds tested. Strains resistant to one macrolide were resistant to all macrolides; however, not all macrolide-resistant strains were resistant to clindamycin, and 32 macrolide-resistant (MICs, > or = 28 microg/ml), clindamycin-susceptible (MICs, < or = 0.25 microg/ml) strains were encountered. Time-kill testing of six strains showed similar killing kinetics for all compounds, with 99.9% killing of all strains observed with the compounds only at or above the MIC after 24 h.